2011
DOI: 10.1103/physrevc.84.034616
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic self-energy calculations and dispersive optical-model potentials

Abstract: Nucleon self-energies for 40,48,60 Ca isotopes are generated with the microscopic Faddeev-randomphase approximation (FRPA). These self-energies are compared with potentials from the dispersive optical model (DOM) that were obtained from fitting elastic-scattering and bound-state data for 40,48 Ca. The ab initio FRPA is capable of explaining many features of the empirical DOM potentials including their nucleon asymmetry dependence. The comparison furthermore provides several suggestions to improve the function… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
108
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(109 citation statements)
references
References 47 publications
1
108
0
Order By: Relevance
“…While this step allows the interpretation of the optical potential as representing the nucleon self-energy, it was also shown that observables like the nuclear charge density cannot be described in detail. By analyzing theoretically calculated self-energies for Ca isotopes which include long-range [23] and short-range correlations [24], it was possible to clarify the importance of representing the imaginary part of the optical potential also in terms of non-local ingredients. These insights have recently led to an extension of the dispersive optical model formalism to explicitly include non-locality [25,26] in the real and imaginary part of the self-energy specifically for the 40 Ca nucleus.…”
Section: Introductionmentioning
confidence: 99%
“…While this step allows the interpretation of the optical potential as representing the nucleon self-energy, it was also shown that observables like the nuclear charge density cannot be described in detail. By analyzing theoretically calculated self-energies for Ca isotopes which include long-range [23] and short-range correlations [24], it was possible to clarify the importance of representing the imaginary part of the optical potential also in terms of non-local ingredients. These insights have recently led to an extension of the dispersive optical model formalism to explicitly include non-locality [25,26] in the real and imaginary part of the self-energy specifically for the 40 Ca nucleus.…”
Section: Introductionmentioning
confidence: 99%
“…Ab initio many-body methods based on coupled cluster (CC) [1][2][3][4][5][6][7][8][9][10], self-consistent Dyson-Green's function (SCDyGF) [11][12][13][14][15] and in-medium similarity renormalization group (IMSRG) [16,17] techniques have been intensively developed in the last ten years to address nuclei up to mass A ∼ 130 [18]. However, these important developments have been limited until recently to doubly closed-(sub)shell nuclei plus those accessible via the addition and removal of one or two nucleons.…”
Section: Introductionmentioning
confidence: 99%
“…[15]. The introduction of nonlocality in the imaginary part of the self-energy is well-founded theoretically both for long-range correlations [18] as well as short-range ones [19]. Its implied ℓ-dependence is essential in reproducing the correct particle number for protons and neutrons.…”
mentioning
confidence: 99%
“…[18,19], we allow for different nonlocalities above and below the Fermi energy, otherwise the symmetry around this energy is essentially maintained by the fit. The values of the nonlocality parameters β appear reasonable and range from 0.64 fm above to 0.81 fm below the Fermi energy for volume absorption.…”
mentioning
confidence: 99%